The anterior cruciate ligament can become hypertrophied in response to mechanical loading: A magnetic resonance imaging study in elite athletes - Beaulieu, M. L.; DeClercq, M. G.; Rietberg, N. T.; Li, S. H.; Harker, E. C.; Weber, A. E.; Ashton-Miller, J. A.; Wojtys, E. M. (The American Journal of Sports Medicine, 2021)
Background: Evidence, mainly from animal models, suggests that exercise during periods of pubertal growth can produce a hypertrophied anterior cruciate ligament (ACL) and improve its mechanical properties. In humans, the only evidence of ACL hypertrophy comes from a small cross-sectional study of elite weight lifters and control participants; that study had methodological weaknesses and, thus, more evidence is needed.